Improved wear resistance moderate abrasion gray cast iron 3.5% copper alloyed austempered at 300 ° C - Rosario Francia, Samuel (2012)
Manufacturing parts cast iron covers a very large field of machinery industry. These materials are iron-carbon alloys, with high percentages of carbon and designated under the name of foundries as this is the industrial process of manufacture thereof. The highest percentage of carbon makes the melting temperature of these is less than that of the steels and also a greater flow of liquid material is achieved which allows the filling of smaller thickness pieces of complex shapes and have improved castability . Moreover, the lower melting temperature allows the metal-mold interaction is less aggressive and thus can obtain a better surface quality parts. Its low cost, and this excellent castability, have led to extensive development of these alloys in applications such as engine blocks, shirts piston, gears, valve bodies, auto parts and many other parts for industrial use. The choice of material is based on properties that can be achieved in each case. In high strength castings seek the best values ​​in their mechanical properties, and these derive from the same constituent structure. The metallurgical engineering in the area of ​​materials studied the ways to get the most appropriate structure to achieve these properties, using techniques and procedures alloys suitable manufacturing. We emphasize the latter because the mechanical properties are not the product formulations more or less sophisticated chemical composition. The manufacturing technique is so important and that the addition of alloying elements, or rather, the combination of both is the way to achieve the best results.